Evaluation of Community Health Center Management Information System (SIMPUS), Primary Care (P Care), and Bridging Data System in Sukoharjo District - Agung Kurniawan; Didik Tamtomo; Bhisma Murti (Journal of Health Policy and Management, 2017)
Background: Community health center (puskesmas) management information system or often referred to as SIMPUS is a local health system aimed at providing health information at primary health care level. P Care (Primary Care) application is an information system that is designed to serve BPJS patients. The bridging system links SIMPUS with P care application. These three systems have been used in all puskesmas in Sukoharjo district since 2017. This study aimed to evaluate the implementation of community health center management information system (Simpus), Primary Care (P Care), and bridging data system, in Sukoharjo District, Central Java.  Subjects and Method: This was a qualitative study. The study was conducted in Sukoharjo, Kartasura, Bendosari, Mojolaban community health centers, in Sukoharjo District, Central Java, from October to December, 2017. Four community health centers were selected randomly from 13 community health centers in Sukoharjo. The dependent variables were information service, performance, efficiency, and security. The independent variable was health information system (SIMPUS, P care, and bridging system). The data were collected by in-depth interview, direct observation, and document review. Data credibility was checked by triangulation method.Results: Three health information systems (SIMPUS, P care, and bridging system) have been implemented in Sukoharjo District. However, their performance is yet to be improved. Loading time was lengthy and error often occured. Patients often complained of the lengthy service. Some items in the information system form were left blank. Data entry occasionally was inconsistent with examination outcome. Security system of the health information existed, but sometimes unauthorized individuals can access and use that information. There was a lack of human resources and hardware. The health information system had not met the information need.Conclusion: Three health information systems (SIMPUS, P care, and bridging system) have been implemented in Sukoharjo District. However, their performance is yet to be improved. Some obstacles have yet to be resolved.Keyword: evaluation, SIMPUS, P care application, bridging systemCorrespondence: Agung Kurniawan. Masters Program of Public Health,  Jl. Ir. Sutami No. 36A Surakarta 57126, Jawa Tengah. E-mail: agungkurniawan991@gmail.com. Mobile +6285257292206.Journal of Health Policy and Management (2017), 2(2): 157-164https://doi.org/10.26911/thejhpm.2017.02.02.07